In vivo manipulation of muscle shape and tendinous stiffness affects the human ability to generate torque rapidly. Issue 2 (15th December 2020) - Monte, Andrea
Abstract : New Findings: What is the central question of this study? What are the determinants of muscle belly gearing, and how does it affect the torque rise? What is the main finding and its importance? Change in muscle thickness of the gastrocnemius medialis is related to variations in belly gearing. Belly gearing has a key role in the rise of muscle torque and rate of torque development (RTD). Besides, the increase of tendinous tissue stiffness could increase the torque rise as well, and in turn, the RTD. However, changes in the tendinous tissue stiffness showed no effects on muscle fascicle behaviour, suggesting a possible uncoupling between muscle and tendon mechanical properties. Abstract: During fixed‐end contractions, muscles bulge in thickness and/or width to maintain a constant volume, whereas tendons lengthen over the entire contraction period. These dynamic changes play a key functional role in modulating the generated torque. However, the literature has revealed a limited understanding of in vivo dynamic muscle–tendon changes during rapid contractions. Therefore, this study aimed to investigate the determinants of belly gearing (belly velocity/fascicle velocity) and its effects on rapid torque production during in vivo fixed‐end contractions. Twenty healthy males were recruited for the study. Muscle shape and tendon stiffness were manipulated by applying a transverse load (2–10 kg) and an ankle rotation manoeuvre, respectively. Ultrafast‐ultrasound was employed to quantify medial gastrocnemius architecture during evoked contraction and a dynamometer was used to measure the muscle torque and quantify the rate of torque development (RTD). Torque and RTD diminished by transverse load application, whereas they increased during the ankle rotation manoeuvre. Belly gearing declined with increasing transverse load but was unaffected by tendinous stiffness variations. Alterations in belly gearing were strongly related to variations in muscle thickness throughout any load applied and affected the torque rise rapidly. In contrast, changes in tendinous tissue stiffness affected the torque rise only but did not modify the muscle shape. These data may suggest that concurrent manipulation of the tendinous tissue stiffness and muscle shape does not affect the explosive rise in torque capacity, suggesting a possible uncoupling between mechanical properties of muscle and tendon. Abstract :